Discourses of Identity in the Tension of Collision of Civilizations - Aleksandravičius, Vygandas (Sociologija. Mintis ir veiksmas, 2001)
The article reflects on the role of the principle of Identity in constitution of particular civilizational models. It attempts to demonstrate the monologous character of the particular Western and Balkan civilizational identities, what attributed to their collision in Kosovo. The principal differences in constitution of Western and Balkan civilizations and their close geopolitical situation created high tension, which discharged in the dramatic conflict, impossible to resolve in discoursive mode due to the lack of common discoursive background. The necessities to distance us from direct identification with one or another expansive identity model was the condition for a reflection and evaluation of the conflict. The poststructuralist critique of the principle of identity, favoring the alternative “thinking based on difference”, decisively contributed to the theoretical background of the phenomenological insights of this text. The collision between the Western and Balkan civilizations was depicted through different planes and from diverse angles as inevitable, unless the will to sustain their particular identities in subjecting the Other were not renounced. Deleuzian interpretation of Michel Tournier’s novel “Friday, or the Limbs of Pacific” provided with a broad insight on the possibility of thinking, based on the reality of difference. Ideas of distinctive American thinker Alphonso Lingis and Lithuanian philosopher Arvydas Šliogeris provided with a basis for delineating vectors of the non-violent constitution of dialogue, whereof a new kind of an inaggressive identity might emerge.
Keywords: principle of identity; civilizational conflict; Western civilization; Balkan civilization; Michel Tournier; Alphonso Lingis; Arvydas Šliogeris